(untitled) (Scientific journal of the Fergana State University, 2024)
A method has been developed for the synthesis of a complex compound of zinc acetate with 2-mercaptobenzthiazole in a molar ratio of 1:3. The composition and structure of the synthesized complex were determined by the methods of elemental, X-ray phase, derivatographic analysis, IR spectroscopy, SEM-EDX. It has been established that coordination with metal ions occurs through sulfur atoms of the C-S group and nitrogen of the thiazole ring